2020
DOI: 10.3390/microorganisms8060837
|View full text |Cite
|
Sign up to set email alerts
|

Combined Application of Bacteriophages and Carvacrol in the Control of Pseudomonas syringae pv. actinidiae Planktonic and Biofilm Forms

Abstract: Pseudomonas syringae pv. actinidiae (Psa) is the causative agent of the bacterial canker of kiwifruit (Actinidia spp.). Phage therapy has been suggested as a viable alternative approach to controlling this disease, but its efficacy is limited by the emergence of phage-resistant mutants. Carvacrol is an essential oil that may be useful for the control of Psa. Combination therapies can be used to overcome resistance development. Here, the combination of phages (single phage suspensions of phages PN05 and PN09, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Phage cocktail persistence in the open field could be improved with specific formulations [ 9 ] and their action can be increased in synergy with the addition with other compounds such as carvacrol [ 20 ] and garlic extract [ 24 ]. Additionally, the phages we isolated can be a useful source of endolysins as an alternative Psa and Pph biocontrol method [ 78 ]; the vast number of functionally uncharacterized ORFs they encode could contribute to further control approaches once their role is elucidated, urging a vast effort to assign function to the unprecedented proteomic diversity harbored by phages [ 67 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phage cocktail persistence in the open field could be improved with specific formulations [ 9 ] and their action can be increased in synergy with the addition with other compounds such as carvacrol [ 20 ] and garlic extract [ 24 ]. Additionally, the phages we isolated can be a useful source of endolysins as an alternative Psa and Pph biocontrol method [ 78 ]; the vast number of functionally uncharacterized ORFs they encode could contribute to further control approaches once their role is elucidated, urging a vast effort to assign function to the unprecedented proteomic diversity harbored by phages [ 67 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…syringae pathovars porri [ 11 ], aesculi [ 12 ] and morsprunorum [ 13 , 14 ]. Several studies have described phages that could potentially be used to control Psa [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] and Pph [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the commercially available phage Φ6 was also effective, both in vitro and ex vivo, particularly against two highly aggressive Psa strains [92]. Similarly interesting, in a recent study, it has been shown that the combination of phages PN05 and PN09 and the natural antimicrobial carvacrol (2.0 mg/mL) controlled Psa regrowth for more than 40 h, preventing the emergence of phage-resistant mutants and controlling biofilm development [93].…”
Section: Fruit Treesmentioning
confidence: 90%
“…According to the method of Ni [ 30 ], Psa was incubated to OD 600 values of 0.6–0.8. Different treatment solutions were mixed with 300 µL of bacterial suspension in 96-well plates to give the final concentrations of ethylicin of 0, 1.80, 2.70, 3.60, and 4.50 μg/mL at 28 °C for 72 h to form biofilms, and each treatment was repeated six times.…”
Section: Methodsmentioning
confidence: 99%